The Importance of Teaching Culture to Develop the Interest and Competence of Iraqi EFL Learners - Nesrallah, Omar (Opción, 2019)
Teaching culture ought to be a important piece of teaching English as a for- eign language since one of the principle aims of teaching a foreign language is intercultural communicative competence (ICC)by which Interest and Com- petence will increase. There is a well known saying in English “acquisition of knowledge in another language is like acquiring a new life.” Many Iraqi EFL learners have a direction of Internalized Foreign Language knowledge, the may experience issues utilizing this knowledge in various settings. This is because of numerous interactive factors influencing their execution, for the most part lack of target culture perceptions. The detailed study is expected to distinguish the culture perspectives appropriate to be coordinated into the Iraqi EFL classrooms, scan for the sources whereupon the understudies get their knowledge of the objective culture and analyze their frames of mind to- wards it and the capacity to accomplish something effectively or proficiently. This examination was directed to three fundamental classifications of subjects the will be the understudies, instructors and specialists in the field of Teaching EFL.